Electronic Word Of Mouth On Visiting Decisions: Case Study On Google Review Lokawisata Baturraden - Wulandari, Wisi; Sianturi, Albert; Rahmadiani, Alma; Nurinto, Bagas; Raudhatul, Khofifah J; Marsha, Aurellia; Rizqy, Megaswara; Yulia, Salsabila M (Journal of Tourism, Hospitality and Travel Management, 2023)
This study aims to discuss how the influence of Electronic Word of Mouth on the Google Review platform results in decisions for tourists who will visit a tourist attraction. This research was conducted on 7 - 9 November 2022, located at Lokawisata Baturaden. This study uses a quantitative research method, with the data obtained will be rated on a Likert scale from a sample of 100 tourists who have decided to visit after receiving information in the form of reviews from Google Reviews. Regarding the sampling, the purposive sampling technique. The analytical method used in this study is descriptive analysis.